Comparative effects of nitrogen fertigation and granular - Bryla, D R (2011)
Comparative effects of nitrogen fertigation and granular fertilizer application on growth and availability of soil nitrogen during establishment of highbush blueberry David R. Bryla1* and Rui M. A. Machado2 1 Horticultural Crops Research Unit, Agricultural Research Service, U.S. Department of Agriculture, Corvallis, OR, USA 2 Departamento de Fitotecnia, Instituto de Ciências Agrárias e Ambientais Mediterrânicas, Universidade de Évora, Évora, Portugal A 2-year study was done to compare the effects of nitrogen (N) fertigation and granular fertilizer application on growth and availability of soil N during establishment of highbush blueberry (Vaccinium corymbosum L. “Bluecrop”). Treatments included four methods of N application (weekly fertigation, split fertigation, and two non-fertigated controls) and four levels of N fertilizer (0, 50, 100, and 150 kg·ha−1 N). Fertigation treatments were irrigated by drip and injected with a liquid urea solution; weekly fertigation was applied once a week from leaf emergence to 60 d prior to the end of the season while split fertigation was applied as a triple-split from April to June. Non-fertigated controls were fertilized with granular ammonium sulfate, also applied as a triple-split, and irrigated by drip or microsprinklers. Weekly fertigation produced the smallest plants among the four fertilizer application methods at 50 kg·ha−1 N during the first year after planting but the largest plants at 150 kg·ha−1 N in both the first and second year. The other application methods required less N to maximize growth but were less responsive than weekly fertigation to additional N fertilizer applications. In fact, 44–50% of the plants died when granular fertilizer was applied at 150 kg·ha−1 N. By comparison, none of the plants died with weekly fertigation. Plant death with granular fertilizer was associated with high ammonium ion concentrations (up to 650 mg·L−1) and electrical conductivity (>3 dS·m−1) in the soil solution. Early results indicate that fertigation may be less efficient (i.e., less plant growth per unit of N applied) at lower N rates than granular fertilizer application but is also safer (i.e., less plant death) and promotes more growth when high amounts of N fertilizer is applied.